Essential Characteristics of the Phenomenon «Reflection» in Psychological and Pedagogical Researches - Marusynets’, Marjana (Pedagogical Discourse, 2013)
The article presents the psychological and pedagogical research of the essence of phenomenon of «reflection». Kinds of reflection (self-reflection, system, personal), as well as types (regulatory defining, synthesizing, creative) are revealed, their essential characteristics, mechanisms and functions are denoted. The role of personal reflection as a process of getting self-knowledge through the personal knowledge analisis is emphasized, attitudes, experiences and understanding of how a person is perceived and estimated by the other subjects of interaction are also clarified.